1996
DOI: 10.1007/bf01369673
|View full text |Cite
|
Sign up to set email alerts
|

A highly variable STR at the D12S391 locus

Abstract: A total of 103 fragments in the STR D12S391 locus were sequenced. 24 different alleles were found which can be grouped into 12 allelic classes based on the total number of repeats. The structure of this compound STR consists of blocks of (AGAT) and (AGAC) repeats with a consensus structure (AGAT)8-17 (AGAC)6-10 (AGAT)0-1. Whereas shorter alleles only have (AGAT) repeats, > 225 bp alleles are more complex, having two motifs (AGAT) and (AGAC). Population data showed that this to be a highly polymorphic STR with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 15 publications
2
39
0
Order By: Relevance
“…These 6-dye multiplex assays co-amplify the 22 polymorphic STR markers D1S1656, D2S441, D2S1338, D3S1358, D5S818, D7S820, D8S1179, D10S1248, D12S391, D13S317, D16S539, D18S51, D19S433, D21S11, D22S1045, CSF1PO, FGA [FIBRA], TH01 [TC11], TPOX, vWA, SE33 [ACTBP2], and DYS391, the gender-specific Amelogenin and the Quality Sensor. All genetic loci have been characterized in numerous studies by other laboratories as examples: [5][6][7]. As a special feature, both kits contain an internal PCR control (Quality Sensor QS1 and QS2), which provides valuable data without affecting PCR performance, even in the case of low DNA content samples.…”
Section: Introductionmentioning
confidence: 99%
“…These 6-dye multiplex assays co-amplify the 22 polymorphic STR markers D1S1656, D2S441, D2S1338, D3S1358, D5S818, D7S820, D8S1179, D10S1248, D12S391, D13S317, D16S539, D18S51, D19S433, D21S11, D22S1045, CSF1PO, FGA [FIBRA], TH01 [TC11], TPOX, vWA, SE33 [ACTBP2], and DYS391, the gender-specific Amelogenin and the Quality Sensor. All genetic loci have been characterized in numerous studies by other laboratories as examples: [5][6][7]. As a special feature, both kits contain an internal PCR control (Quality Sensor QS1 and QS2), which provides valuable data without affecting PCR performance, even in the case of low DNA content samples.…”
Section: Introductionmentioning
confidence: 99%
“…The STR polymorphisms HUMTH01 [1,2], HUMVWA31 /A [3,4], HUMF13A1 [5], HUMFES / FPS [6], D12S391 [7], HUMFIBRA / FGA [8] are increasingly used for paternity testing and forensic identification. All of these systems consist of tetranucleotide repeat units with some variants.…”
Section: Introductionmentioning
confidence: 99%
“…Population data revealed that both loci are very polymorphic and display a considerable number of alleles. Due to the presence of (AAAG) and (GAAG) repeats, the STR system at locus D11S488 could be classified as a compound STR, such as locus D11S554 (Adams et al 1993) or locus D12S391 (Lareu et al 1996). In contrast the STR system at locus D8S639 has intermediate microvariations with similiarities to complex STR sys- tems, such as locus HumACTBP2 Möller and Brinkmann 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Simple repeats contain units of identical length and sequence, compound repeats comprise two or more adjacent simple repeats, complex repeats may contain several repeat blocks of variable length, along with variable intervening sequences (Urquhart et al 1994). Very often a high polymorphism is associated with considerable sequence variations (Adams et al 1993;Möller and Brinkmann 1994;Brinkmann et al 1996;Lareu et al 1996). Although most STR loci are characterized by a low mutation rate (Weber and Wong 1993), some loci exhibit hypermutability (Talbot et al 1995) and microsatellite instability is found in a variety of neoplasmas (Perucho 1996;Boland 1996) or has been associated with some human genetic disorders (Mahadevan et al 1992).…”
Section: Introductionmentioning
confidence: 99%